High-speed metamagnetic switching of FeRh through Joule heating - Nicholas A. Blumenschein; Gregory M. Stephen; Cory D. Cress; Samuel W. LaGasse; Aubrey T. Hanbicki; Steven P. Bennett; Adam L. Friedman (Scientific Reports, 2022)
Abstract Due to its proximity to room temperature and demonstrated high degree of temperature tunability, FeRh’s metamagnetic ordering transition is attractive for novel high-performance computing devices seeking to use magnetism as the state variable. We demonstrate electrical control of the antiferromagnetic-to-ferromagnetic transition via Joule heating in FeRh wires. The magnetic transition of FeRh is accompanied by a change in resistivity, which can be probed electrically and allows for integration into switching devices. Finite element simulations based on abrupt state transition within each domain result in a globally smooth transition that agrees with the experimental findings and provides insight into the thermodynamics involved. We measure a 150 K decrease in transition temperature with currents up to 60 mA, limited only by the dimensions of the device. The sizeable shift in transition temperature scales with current density and wire length, suggesting the absolute resistance and heat dissipation of the substrate are also important. The FeRh phase change is evaluated by pulsed I-V using a variety of bias conditions. We demonstrate high speed (~ ns) memristor-like behavior and report device performance parameters such as switching speed and power consumption that compare favorably with state-of-the-art phase change memristive technologies.